Diagnostic Value of Erythropoietin Levels in Umbilical Cord Blood in Hypoxic-Ischemic Brain Injury: Clinical Observational Cross-Sectional Study - S. B. Berezhanskaya; M. K. Abduragimova (Кубанский научный медицинский вестник)
Background. In recent years erythropoietin has received particular attention due to the discovery of its important non-haematological effects. Erythropoietin is recognized as a pluripotent glycoprotein, manifesting neurotropic and neuroprotective properties as well as participating in angio-, neuro- and oligodendrogenesis, interferes with the effects of hypoxia-ischemia, oxidative stress and associated with them inflammation and apoptosis in the brain. During fetal hypoxia, the dominant production of erythropoietin switches to the placenta, starting its active synthesis to protect the brain, heart and other vital organs from harmful effects of severe hypoxia.Objectives. The study was aimed at determining the correlation between the severity of hypoxic ischemic brain injury and erythropoietin level in the artery and vein of the umbilical cord.Methods. A clinical observational cross-sectional study was conducted on the basis of the Maternity Hospital, Neonatal Pathology and Pediatric Departments №1 and №2 of the Research Institute of Obstetrics and Pediatrics under the auspices of Rostov State Medical University, Russian Federation. The study included 184 newborns with moderate (group II, n = 78) and severe hypoxic ischemic injury of the central nervous system (group III, n = 42). Group I consisted of 64 children without signs of central nervous system injury in the early neonatal period. Among which, following the maternal medical histories, 40 newborns were allocated to the group with the apparent development of delayed manifestation of neurological pathology. The evaluation of erythropoietin concentration in the umbilical cord blood was conducted separately in the artery and vein with Erythropoietin-EIA-BEST, a set of reagents for the enzyme-linked determination of erythropoietin concentration in the blood serum. Statistical analysis was carried out via MS Excel 2019 (Microsoft, USA), Statistica 12.5, (IBM, USA), SPSS27.001.Results. Erythropoietin concentrations in the blood of the artery and vein of the umbilical cord in the groups of newborns were determined according to the severity of hypoxic-ischemic brain injury. The authors of the study showed the correlation between the “maternal-placental-fetal” blood flow at 36–40 weeks of gestation, which parameters are important antenatal predictors of the central nervous system injury, and the values of erythropoietin in arterial and venous umbilical cord blood as diagnostic markers.Conclusion. The severity of cerebral abnormalities is determined by a high level of erythropoietin, while a decrease in erythropoietin level with severe cerebral deficit can mark a disabling injury.